Digital economy development in Kyrgyzstan: challenges and opportunities ("Journal "U". Economy. Management. Finance.", 2024)
The article is dedicated to the development of the digital economy in Kyrgyzstan, analyzing current trends and prospects of digital transformation in the country. The article discusses key areas of digitalization such as e-commerce, financial technologies, e-government, and the implementation of digital solutions in education and healthcare. Special attention is given to the opportunities for increasing business competitiveness, improving the quality of public services, and developing human capital. At the same time, the authors highlight significant challenges, such as the low level of digital literacy among the population, infrastructure issues, cybersecurity concerns, and the lack of an effective legislative framework. The article emphasizes the need for a comprehensive approach to addressing these problems, including the development of internet infrastructure, increasing digital skills, and creating legal and economic conditions to stimulate innovation. In conclusion, it is stated that the successful development of the digital economy in Kyrgyzstan opens new opportunities for economic growth and modernization in various sectors of the country. To achieve this, it is necessary to improve infrastructure, develop the digital skills of the population, enhance legal regulation, and create conditions for innovation, which will enable Kyrgyzstan to take a leading role in the digital transformation of Central Asia, stimulating economic growth and attracting investments.
Keywords: Digital economy; digitalization; information and communication technologies (ICT); cybersecurity; e-commerce; e-government